An Improved Protection Of High Voltage Air Line Using Differential Relays - Ariyanto Gultom; Parlin Siagian; Amani Darma Tarigan (Sean Institute, 2024)
A static electrical device is like a power transformer, one of the functions of which is to transfer one power circuit to another circuit, either changing the voltage without having to change the frequency. This paper described a Protection is a system in electricity and has a function as an isolate, breaker and separator if there is a disturbance. The working principle of the differential relay is to compare the vector I1 of the primary side current with I2 of the secondary side current.